2000
DOI: 10.1046/j.1365-2508.2000.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Adelaide laparoscopic hysterectomy audit (1991–1998): realistic complication rates!

Abstract: Objective To review complications of laparoscopic hysterectomy occurring in a citywide population of approximately 1 million people. Design All laparoscopic hysterectomy cases were analysed retrospectively independently of the surgeons involved. Setting All private and public hospitals (n = 19) in metropolitan Adelaide, South Australia. Subjects 1904 patients over the period 1991–98. Interventions The majority of cases involved a combined laparoscopic and vaginal approach with a proportion of total laparoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 5 publications
(5 reference statements)
3
15
0
Order By: Relevance
“…Our rates of ureteric (0.2%) and bladder (0.2%) injury are comparable to other studies reporting 0.2–0.4% ureteric and 1.0–1.8% bladder injuries 4,21,22 . Prior cesarean section, prior pelvic surgery and endometriosis have been cited as the main determinants of intra‐ and postoperative complications 23 .…”
Section: Discussionsupporting
confidence: 85%
“…Our rates of ureteric (0.2%) and bladder (0.2%) injury are comparable to other studies reporting 0.2–0.4% ureteric and 1.0–1.8% bladder injuries 4,21,22 . Prior cesarean section, prior pelvic surgery and endometriosis have been cited as the main determinants of intra‐ and postoperative complications 23 .…”
Section: Discussionsupporting
confidence: 85%
“…[7,[29][30][31][32][33] No urinary tract damage was observed in the VH group; however, in the 2D TLH group, two patients reported ureter injury and one patient revealed vesicovaginal fistula; in the 3D TLH group, ureter injury developed in one patient in our study. We found urinary injury ratios for 2D and 3D TLH groups (2.9% and 2.4%, respectively) to be higher than the 0.2%-0.4% values for TLH as mentioned in other studies; [34,35] however, we did not observe any significant difference between the 2D and 3D TLH groups in terms of the urinary injury rates. Urinary bladder injury rates for 2D and 3D TLH groups (1.4% and 0%, respectively) in our study were found to be similar with the reported values (1.0% and 1.8%, respectively) in other studies.…”
Section: Discussionsupporting
confidence: 48%
“…Estimated blood loss remained fairly constant and dropped from 274 mL to 213 mL whereas the rate of hemorrhage increased from 3.5% to 4.7%. 16 This difference could be explained by the circumstances: the Adelaide audit was undertaken when the technique was fairly new and spread rapidly. In our study, we found a significant reduction of hemoglobin drop after 30 cases as a sign of the learning effect.…”
Section: Discussionmentioning
confidence: 99%